Measuring Optimal Portfolio for Selected Financing Contracts of Islamic Banks in Indonesia - Wiranatakusuma, Dimas Bagus; Nindy, Aurellia Azh (The International Journal of Financial Systems, 2023)
Financing is the primary factor in boosting the operational performance of Islamic banks. Financing is a productive asset that is susceptible to risk. The research mainly aims to find the optimal limit that can be tolerated in order to improve the operational performance of Islamic banks. The research objects cover Mudharabah, Musharakah, Murabahah, and Istishna financing contracts. This study shows the optimal level of Mudharabah growth should be between 1% and 4%, Musharakah growth should be between 3% and 6%, Murabahah growth should be between 2% and 3.6%, and Istishna growth should be between 1% and 3.7%.